Proactive Value Co-Creation via Structural Ambidexterity: Customer Success Management and the Modularization of Frontline Roles. (November 2021) - Hochstein, Bryan; Chaker, Nawar N.; Rangarajan, Deva; Nagel, Duane; Hartmann, Nathaniel N.
An increasing number of business-to-business (B2B) service firms have transitioned to recurring revenue-based solutions. These subscription B2B solutions are becoming increasingly common, yet offer challenges for long-term renewal if value is not consistently realized by the customer. To address this concern, customer success (CS) management has emerged. CS management is based on regular proactive action taken by the seller to (a) educate, prepare, and engage customers for value co-creation; (b) demonstrate the value delivered by the solution; and (c) provide a channel for advocacy on behalf of customers within the service-providing firm. Our findings highlight the under-researched topic of CS in B2B settings. Specifically, we propose the CS function and role as a structural alternative to within-person (i.e., cross-functional) ambidexterity and emphasize the ability of a CS focus by service firms to complement existing firm operations in value creation efforts. Our case study analysis provides a multilevel perspective (i.e., executive, functional role employees, and customers) via in-depth interviews that offer unique insights on "how parts of the service-sales system work together." Overall, CS is growing as a practice that propagates value to the customer via ongoing success with solutions while improving service-firm renewal and growth of subscription business.